Human Resource Development and the Needs of Training Department: A Case Study on Malaysia Packaging Sdn. Bhd. - Liaw, Khing Hong (1999)
The lacking of the long-tenn human resource development plan for Malaysia packaging Ind Bhd (MA yP AK) had caused the company to suffer from many problems like high turnover, high rejection rate, lack of skilled workforce, weak Sales and Marketing personnel and others. With the increasing demand from the customers for better quality products and services, had put MA yP AK in the difficult situation to coup with the demands. Without quality and competence workforce, the company has difficulty to coup with the increasing demand from the customers. The important of training in the human resource development was iden